Analisis Penggunaan Repository Perpustakaan Universitas Medan Area (UMA) dengan Menggunakan Metode iSystem Usability Scale (SUS) - Trie Ananda (Universitas Negeri Padang, 2023)
In order to ascertain the usage of the University of Medan Area Library's Repository system, this research aims to evaluate the level of Repository system usage at the Medan Area Library using the System Usability Scale (SUS) methodology. A total of 50 respondents, comprising librarians and students from the University of Medan Area, were selected as the research subjects. This study involved testing through validity assessments, reliability assessments, and an analysis of the SUS methodology. The research findings elucidate that based on the data analysis from the recapitulation of questionnaire testing results using the SUS methodology, encompassing Acceptability, Grade Scale, and Adjective Rating facets, the outcomes indicate that the range of user Acceptability towards the University of Medan Area Library's repository website is in the Marginal High grade range, with the Grade Scale level falling in the D category, and the Adjective Rating level positioned in the nearly Good (OK) category. These findings potentially indicate the success of utilizing the University of Medan Area Library's Repository using the SUS methodology. Furthermore, it is also discernible that the SUS methodology exerts a positive influence on system usage. This is substantiated by the observed increase in the SUS score, reaching 65. Hence, it can be inferred that the University of Medan Area Library's repository website still requires further evaluation and development to enhance its usability optimally.